A 3D pantographic metamaterial behaving as a mechanical shield: Experimental and numerical evidence - Ciallella, Alessandro; Giorgio, Ivan; Barchiesi, Emilio; Alaimo, Gianluca; Cattenone, Alberto; Smaniotto, Benjamin; Vintache, Antoine; D'Annibale, Francesco; dell'Isola, Francesco; Hild, François; Auricchio, Ferdinando (Materials & Design, 2024)
Multilayer pantographic metamaterials, in short, pantographic blocks, have shown peculiar mechanical behavior, especially when their constitutive hinges are revolving (i.e., perfect) joints. The pantographic block, which is the subject of the present paper, has been printed using a Powder Bed Fusion technology and its hinges may be modeled as perfect ones. In the reported in situ 3-point flexural test, the predictions obtained by second gradient models for its mechanical response are shown to be experimentally consistent thanks to measurements via Digital Volume Correlation. The deformation applied by the upper central support is almost entirely shielded by the pantographic block, namely, the specimen barely crosses through the reference bottom plane defined by the lower lateral supports, even when subjected to very large 1 deformations. The mathematical model employed herein captures this observation in terms of a nonlinear 'arching' effect activated in the beams of the pantographic structure, provided elastic locking is introduced to prevent pantographic zero-energy modes.